Preventing antibody positive delayed hemolytic transfusion reactions in sickle cell disease: Lessons learned from a case. Issue 5 (22nd March 2022) - Rankin, Alexander; Webb, Jennifer; Nickel, Robert Sheppard
Abstract: Introduction: Red blood cell (RBC) transfusions are important in the management of patients with sickle cell disease (SCD). However, a potentially catastrophic complication of transfusion in this population is the delayed hemolytic transfusion reaction (DHTR). The pathophysiology of all DHTRs is not understood, but some are known to be caused by an anamnestic resurgence of RBC alloantibodies. Case presentation: A child with SCD transfused for acute chest syndrome re‐presented a week after hospital discharge with severe anaemia, hemolysis, and a newly detected anti‐E. This patient had been previously transfused years ago at an outside institution and the anti‐E had not been previously documented. Discussion: The presented case of an antibody positive DHTR illustrates several concepts critical to the prevention of this complication. RBC alloantibodies must be detected and this information must be shared. Prophylactic C/c, E/e, K antigen matching is helpful for patients with SCD, but systems must be in place to identify these patients. Patients transfused at multiple different hospitals are especially at risk for this complication and efforts are needed to prevent them from suffering a DHTR.